Securing Data Deduplication Using Convergent Encryption Algorithm - Kailash Patidar, K. P. Saurabh (Mathematical Statistician and Engineering Applications, 2022)
Deduplication is a technique for minimizing data storage needs by getting rid of duplicate copies of files. The exponential growth in both the number of users and the amount of data stored in the cloud has made data deduplication an absolute must for cloud service providers. Their cloud providers will save money on storage and data transport by keeping only one copy of duplicate data. The goal is to explicitly address the issue of permitted data deduplication in order to better preserve data security. In addition to the data itself, we also take into account the varying levels of access each person has in the duplication check process. We have numerous novel deduplication architectures to provide approved duplicate check in a hybrid cloud environment. To prove the scheme is safe according to the suggested security model's definitions, a security analysis must be carried out. We develop a prototype of the approved duplication check mechanism we propose and test it on a testbed.